Quantifying the Impact of Severe Weather Conditions on Online Learning During the COVID-19 Pandemic - Lagmay, Ezekiel Adriel (Archīum Ateneo, 2021)
From October to November 2020 the Philippines was struck by eight typhoons, two of which caused widespread flooding, utilities interruptions, property destruction, and loss of life. How did these severe weather conditions affect online learning participation of students pursuing their undergraduate and graduate studies in the midst of the COVID-19 pandemic? We used CausalImpact analysis to explore September 2020 to January 2021 data collected from the Moodle Learning Management System data of one university in the Philippines. We found that overall student online participation was significantly negatively affected by typhoons. However, the effect on participation in Assignments and Quizzes were not significant. These findings suggested that students continued to invest their time and energy on activities that have a direct bearing on their final grades.